Accounting for Outcomes in Participatory Urban Governance through State–Civil-society Synergies - Antonio Postigo (Urban Studies, 2011)
Over the past two decades, Latin America has been home to a large number of experiences in local participatory governance. Drawing on spatial conceptualisations of participation and models of state–society synergy, this article explores how power dynamics within and between civil society and the state have shaped the emergence, evolution and outcomes of participatory budgeting processes in three Latin American cities: Porto Alegre, Montevideo and Mexico City. In line with polity-centred analyses, the study supports the fundamental role played by the state in opening spaces of participatory governance in all three cases. These participatory experiences had a transformative effect on societal spaces and actors contributing to the mobilisation and democratisation of civil society. In turn, increasing activism by an autonomous and politically conscious citizenry boosted the efficiency, transparency and legitimacy of the polity and the local institutions of representative democracy.
Keywords: 330